Advancing transboundary basin cooperation through multistakeholder platforms and modeling: Insights from the 7th International REMCO Conference - Nehring, Ryan; Mgudlwa, Maliviwe; Lautze, Jonathan F. (CGIAR, 2023)
Researchers from the CGIAR Initiative on NEXUS Gains participated in the 7th International River and Environmental Management Cooperation (REMCO) Conference in November, with the theme of “promoting operational transboundary cooperation”. This event, in Ezulwini, Eswatini, brought together more than 100 participants from across the region and the world to discuss the primary challenges and advances in the governance of the Incomati Basin.